The Dilemma of Forecasting in International Relations - The Limits of Theories and Methodological Difficulties - Assistant Professor Dr. Imad Jassem Muhammad, (The college of law and political science journal, 2023)
The Dilemma of Forecasting in International Relations - The Limits of Theories and Methodological Difficulties